The effects of urbanisation on non-timber forest product dependencies : a case study of three settlements in the Chobe district of northern Botswana - Joos-Vandewalle, Stephanie (Department of Environmental and Geographical Science, 2015)
The aim of this study was to investigate the impacts of urbanisation on the use of, and access to, NTFPs in three settlements in the Chobe District of northern Botswana. Specific objectives were to determine the extent of NTFP use occurring in these areas; the purposes of use; the factors that influence use and access in the rural/urban context, particularly government rules and regulations; and implications for future NTFP use in this region. Research was conducted in three settlements: Kasane, Kazungula and Lesoma. Kasane is an urban town, Kazungula is less urbanised and Lesoma is a rural village. All areas are surrounded by state-owned Forest Reserves and the Chobe National Park. The study employed both qualitative and quantitative data collection methods including household interviews (30 in Kasane, 30 in Kazungula and 25 in Lesoma), four key informant interviews, two focus groups with youth and the collection of other grey literature relating to government harvest permits and market data. Households in all three areas used NTFPs despite the different rural and urban contexts in which they exist. Kasane and Kazungula showed a less diverse range of resource use, with fuelwood and wild foods the most commonly used resources in all three areas. These resources were used mainly for subsistence purposes. Harvest locations varied but were most commonly in and around the settlements themselves. Households in Kasane and Kazungula expressed the desire to use fewer resources in the future, mainly for conservation reasons, while those in Lesoma wished to use more. The government rules and regulations, particularly the DFRR permit system, were found to restrict resource access. Despite this, households in the more urban areas felt that the laws were necessary while those households in Lesoma thought that the laws conflicted with community livelihood needs. The majority of respondents believed conservation management to be a barrier to resource access as the presence of wild animals and anti- poaching units in the harvesting areas compromised safety. The general absence of resource commercialisation and market opportunities in the settlements, especially the urban towns of Kasane and Kazungula, were other commonly cited barriers to resource access. The perceived degradation of traditional practices due to modernity and urbanisation was evident for most households in all three areas but the actual loss of indigenous knowledge was most apparent in the urban areas. Wider implications for this case study are the application of the findings to further research into the impacts of urbanisation. This study can add to the literature around the implementation of improved urban development strategies, including the reliance on NTFPs and declines in cultural and environmental degradation. Recommendations provided in this study include further investigations into resource use; the application of resource co-management; improved market infrastructure and the implementation of ecotourism and local craft-making projects.